PENGARUH PENGAWASAN, BEBAN KERJA DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN CV TELAGA JERNIH SUNGAI BENDUNG AIR, KAYU ARO: Efrianto, Hendra, Indra Budaya - efrianto, Efrianto; hendra, Hendra; Budaya, Indra (JURNAL ADMINISTRASI NUSANTARA, 2023)
This study aims to determine the effect and magnitude of the influence: Supervision, Workload and Compensation on Work Productivity of Employees of CV. Telaga Jernih Sungai Bendung Air, Kayu Aro Simultaneously and Partially. The population of this study were all employees of CV. Telaga Jernih, totaling 32 people. The data were collected by using a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of this study indicate that supervision has an effect on the work productivity of CV. Telaga Jernih employees, this is evidenced by t count > t table (3.323 > 2.048). Workload affects the work productivity of employees of CV. Telaga Jernih, this is evidenced by t count > t table (3.174 > 2.048). Compensation has an effect on the work productivity of CV. Telaga Jernih employees, as evidenced by t count > t table (2.846 > 2.048). Simultaneously there is a significant influence between supervision, workload and compensation on the work productivity of employees of CV. Telaga Jernih, which can be proven by F count > F table (19.924 > 2.95). The influence of supervision, workload and compensation on work productivity of CV. Telaga Jernih employees is 66.58%. While the remaining 33.42% is explained by other causal factors not examined in this study.